Spectroscopic study of formation, evolution and interaction of M31 and M33 with star clusters. Issue Volume 10:Issue S312(2014) (7th March 2016) - Fan, Zhou; Yang, Yanbin
Abstract: The recent studies show that the formation and evolution process of the nearby galaxies are still unclear. By using the Canada France Hawaii Telescope (CFHT) 3.6m telescope, the PanDAS shows complicated substructures (dwarf satellite galaxies, halo globular clusters, extended clusters, star streams, etc.) in the halo of M31 to 150 kpc from the center of galaxy and M31-M33 interaction has been studied. In our work, we would like to investigate formation, evolution and interaction of M31 and M33, which are the nearest two spiral galaxies in Local Group. The star cluster systems of the two galaxies are good tracers to study the dynamics of the substructures and the interaction. Since 2010, the Xinglong 2.16m, Lijiang 2.4m and MMT 6.5m telescopes have been used for our spectroscopic observations. The radial velocities and Lick absorption-line indices can thus be measured with the spectroscopy and then ages, metallicities and masses of the star clusters can be fitted with the simple stellar population models. These parameters could be used as the input physical parameters for numerical simulations of M31-M33 interaction.